A Colorimetric Dermal Tattoo Biosensor Fabricated by Microneedle Patch for Multiplexed Detection of Health‐Related Biomarkers. Issue 24 (1st November 2021) - He, Rongyan; Liu, Hao; Fang, Tianshu; Niu, Yan; Zhang, Huiqing; Han, Fei; Gao, Bin; Li, Fei; Xu, Feng
Abstract: Detection of biomarkers associated with body conditions provides in‐depth healthcare information and benefits to disease management, where the key challenge is to develop a minimally invasive platform with the ability to directly detect multiple biomarkers in body fluid. Dermal tattoo biosensor holds the potential to simultaneously detect multiple health‐related biomarkers in skin interstitial fluid because of the features of minimal invasion, easy operation, and equipment‐free result reading. Herein, a colorimetric dermal tattoo biosensor fabricated by a four‐area segmented microneedle patch is developed for multiplexed detection of health‐related biomarkers. The biosensor exhibits color changes in response to the change of biomarker concentration (i.e., pH, glucose, uric acid, and temperature), which can be directly read by naked eyes or captured by a camera for semi‐quantitative measurement. It is demonstrated that the colorimetric dermal tattoo biosensor can simultaneously detect multiple biomarkers in vitro, ex vivo, and in vivo, and monitor the changes of the biomarker concentration for at least 4 days, showing its great potential for long‐term health monitoring. Abstract : Simultaneous detection of multiple biomarkers provides in‐depth healthcare information, where the key challenge is to develop a minimally invasive platform. To this end, a colorimetric dermal tattoo biosensor fabricated by a four‐area segmented microneedle patch is developed. The biosensor exhibits color changes in response to biomarker concentration variations, showing its great potential for health monitoring.